2020
DOI: 10.22363/2618-8163-2020-18-4-409-421
|View full text |Cite
|
Sign up to set email alerts
|

Russian-as-a-heritage-language vocabulary acquisition by bi-/multilingual children in Canada

Abstract: The significance of this paper is in its contribution to the innovative and rapidly developing research area of Russian as a heritage language (RHL) around the world. The purpose of the reported study is to explore Russian vocabulary development by bi-/multilingual children acquiring Russian as a heritage language in Canada. The materials come from vocabulary development and non-canonical lexical forms (NCF, earlier known as errors) in the speech of 29 bi-/multilingual children (between the ages of 5 and 6) fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
7
1
Order By: Relevance
“…In a study of narrative production among Canadian child Russian HSs, Makarova and Terekhova (2020) found that HSs produce considerably more lexical non-target responses than their monolingual counterparts. A considerable portion of those lexical non-target responses were phonological, suggesting that HSs can retrieve lexical items but falter at the production stage.…”
Section: Lexical Knowledge Of Hss: Qualitative Competencementioning
confidence: 99%
See 2 more Smart Citations
“…In a study of narrative production among Canadian child Russian HSs, Makarova and Terekhova (2020) found that HSs produce considerably more lexical non-target responses than their monolingual counterparts. A considerable portion of those lexical non-target responses were phonological, suggesting that HSs can retrieve lexical items but falter at the production stage.…”
Section: Lexical Knowledge Of Hss: Qualitative Competencementioning
confidence: 99%
“…HSs are known to use overgeneralizations, such as hypernyms, to indicate a target concept, favoring more generic terms over more precise ones (Kopotev, Kisselev & Polinsky, 2020). Klapicová (2018) similarly found that bilingual children use more non-specific nouns and verbs compared to monolinguals, directly contradicting the tendency toward hyponyms observed by Makarova and Terekhova (2020). By contrast, Ringblom and Dobrova (2019) found analogous patternsthe use of co-hyponyms, holonyms, and definitionsin all child production, both HS and monolingual.…”
Section: Lexical Knowledge Of Hss: Qualitative Competencementioning
confidence: 99%
See 1 more Smart Citation
“…Previous research on RHL addressed certain aspects of vocabulary acquisition based on narrative, experimental, and longitudinal data ( Bar-Shalom and Zaretsky, 2008 ; Gagarina et al, 2014 ; Klassert et al, 2014 ; Ringblom and Dobrova, 2019 ; Makarova and Terekhova, 2020 ; Montanari et al, 2020 ; Czapka et al, 2021 ). Several of the studies have been conducted in Germany, where Russian is one of the most frequently spoken and intensively investigated HLs.…”
Section: Previous Research On Lexical Development In Rhlmentioning
confidence: 99%
“…Several other studies have investigated a different set of lexical parameters in RHL spoken in Canada, Sweden, and the United States. Makarova and Terekhova (2020) analyzed narrative samples of 29 Russian-speaking bilinguals (age 5–6) from Canada and 13 monolinguals from Russia. In addition to the traditional measures of vocabulary development that are also central in the present study (TNW and NDW), the authors provide a qualitative analysis of the bilinguals’ vocabulary and their non-canonical lexical forms.…”
Section: Previous Research On Lexical Development In Rhlmentioning
confidence: 99%